Personality Traits and Administrative Effectiveness of Secondary School Principals in Southwestern Nigeria - Olasunkanmi, ADENIYI Wasiu (Advances in Social Sciences Research Journal, 2014)
The thrust of the paper was to investigate the personality traits and administrative effectiveness of secondary school principals in Southwestern Nigeria. This was with a view to improving administrative skills of secondary school principals. The sample size comprised of 53 principals and 821 teachers who were selected from 53 public secondary schools from four states in Southwestern Nigeria using multistage and purposive sampling techniques. Principals’ Personality Traits Questionnaire” (PPTQ) and Principals’ Administrative Effectiveness Questionnaire” (PAEQ) were the instruments used to collect data from the respondents. Descriptive statistics and chi-square statistics were employed to analyse the data. The results showed that 65.8% of teachers indicated that their principals were very effective. The mostly exhibited personality trait as reported by principals (56.6%) was conscientiousness. Also, the result showed that there existed a significant relationship between personality traits and administrative effectiveness of secondary school principals (χ2 = 42.4, p < 0.05). The study concluded that conscientiousness was the necessary personality trait which predisposed secondary school principals to be effective in discharging their administrative duties.